ЕРТЕК СЮЖЕТИ СТИЛИЗАЦИЯ ТИЙКАРЫНДА ЖҮЗЕГЕ КЕЛГЕН АРАЛЫҚ ДРАМАЛЫҚ ЖАНРЛАР - Қазахбаев, С.С. (FAN va JAMIYAT, 2016)
The article is devoted to the study of the genre of drama in Karakalpak literature for children at the end of the XX-th and the begining of the XXI -century. It deals with the analysis of a fairy tale's plot and characteristic features of different genres of drama. They are such genres as a literary fairy tale drama, a fairy – tale improvisation, a fairy -tale play and a libretto. The author also studies the artistic-ideal and thematic peculiarities of fairy -tales.